Títeres como herramienta para desarrollar el área socio-afectiva, de los niños de primer año de educación general básica, de la escuela de educación básica Ciudad de Loja sección matutina durante el año 2019 - 2020. - Bahamonde Jaramillo, Christian Alexander (2020)
The present investigative work deals about how to develop the socio-affective area through the puppetry tool on children of the First-year Basic general education of Loja city, it had as general objective to determine how puppets assist to develop the socio-affective area of the children of the first year of basic education, scientific methods were used for its development, analytical-synthetic, inductive-deductive, statistic, descriptive and dialectic, and the techniques and tools employed in the research were: the survey applied to 4 teachers and the Ebbe León Gross’s MEET YOUR CHILDREN test applied to 26 parents, which allowed to diagnose the development of the socio-affective area in 26 children, the same ones that constituted the study sample. Regarding the results in the pre-test, it was proven to determine that 92% of children have a regular level, presenting difficulties to socialize, express emotions and share. To support the development of the socio-affective area on the children, it was designed and applied a guide of playful activities denominated “Learning together”, activities were carried out with the children, using the puppets as a didactic resource, and the belief that the puppets are used to the spectacle medium as a simple distraction object but as a key methodological tool of the enrichment of a good learning on the children, is eliminated. Once the activities are executed, they were evaluated with the post-test, concluding that the 65% achieved a good level, favoring the socio-affective area on the children, assisting on a real way to the emotional development; which is rescued in this reThe present investigative work deals about how to develop the socio-affective area through the puppetry tool on children of the First-year Basic general education of Loja city, it had as general objective to determine how puppets assist to develop the socio-affective area of the children of the first year of basic education, scientific methods were used for its development, analytical-synthetic, inductive-deductive, statistic, descriptive and dialectic, and the techniques and tools employed in the research were: the survey applied to 4 teachers and the Ebbe León Gross’s MEET YOUR CHILDREN test applied to 26 parents, which allowed to diagnose the development of the socio-affective area in 26 children, the same ones that constituted the study sample. Regarding the results in the pre-test, it was proven to determine that 92% of children have a regular level, presenting difficulties to socialize, express emotions and share. To support the development of the socio-affective area on the children, it was designed and applied a guide of playful activities denominated “Learning together”, activities were carried out with the children, using the puppets as a didactic resource, and the belief that the puppets are used to the spectacle medium as a simple distraction object but as a key methodological tool of the enrichment of a good learning on the children, is eliminated. Once the activities are executed, they were evaluated with the post-test, concluding that the 65% achieved a good level, favoring the socio-affective area on the children, assisting on a real way to the emotional development; which is rescued in this researching process is the family involvement in the test and pos-test enforcement, from which was reflected in the diagnostic and evaluation of each one of the children, demonstrating that the use of the puppets helped develop the socio-affective areasearching process is the family involvement in the test and pos-test enforcement, from which was reflected in the diagnostic and evaluation of each one of the children, demonstrating that the use of the puppets helped develop the socio-affective area